INVESTMENT ANALYSIS AND MANAGEMENT An Indonesian Adaptation - Hajanirina Andrianantenaina (Journal of Indonesian Economy and Business (JIEB), 2015)
A book review dealing with investment in the field of management. It attempts to offer some adaptation to the local environment in Indonesia as compared with the common USA firm and country characteristics case. Yet, effort have been made to adjust the context to the Indonesian conditons but the US firm cases still prevail. Nevertheless, it is hoped to help local students as well as international students to grasp directly the objective for each course on investment. The adaptation is actually made from the P Charles Jones' previous book on principle of investment issue. We suggest also the advance course as it is highly recommended for students (mostly from undergraduate program to graduate one).